Financial Globalization and Bank Lending: The Limits of Domestic Monetary Policy? - Jin Cao; Valeriya Dinger (Center for Economic Studies and ifo Institute (CESifo), 2018)
We empirically analyze how bank lending reacts to monetary policy in the presence of global financial flows. Employing a unique and novel dataset of the funding modes and currency composition of the full population of Norwegian banks in structurally identified regressions, we show that the efficiency of the bank lending channel is affected when banks can shift to international funding and thus insulate their costs of funding from domestic monetary policy. We isolate the effect of global factors from domestic monetary policy by focusing on the deviation of exchange rates from the prediction of (uncovered and covered) interest rate parity. The Norwegian banking sector represents an ideal laboratory since the exogenous exchange rate dynamics allows for a convincing identification of the relation between lending and global factors.
Keywords: E52; F36; G21; 330; monetary policy; foreign funding channel; bank lending channel; exchange rate dynamics